Upaya Pemerintah dalam Menerapkan Peraturan Pemerintah No. 49 Tahun 2018 Tentang Pegawai Pemerintah Dengan Perjanjian Kerja (P3K) dI Kabupaten Aceh Utara - Rudi Kurniawan; Rasyidin Rasyidin; Muhammad Muhammad; Fidhia Aruni (Jurnal Public Policy, 2020)
This study focuses on efforts to implement Government Decree No. 49 of 2018 concerning civil servants with employment contracts (P3K) in northern Aceh. This study uses descriptive qualitative research methods using data collection methods using observation, interviews, and documentation. The results showed that the government's efforts to implement Government Decree No. 49 to 2018 regarding Civil Servants with Contract of Work (P3K) is carried out with the first phase receiving first aid from PTT staff and the agriculture department, while not accepting it for other groups, although in limited circumstances due to local budget constraints. P3K is very useful for the government in filling gaps in various government institutions or institutions. For the community itself, there are several benefits related to P3K, namely by having multiple records, the income earned will be the same as for a civil servant, will receive the same benefits as a civil servant, the application age is higher and can be reduced to the maximum retirement age.